Taxonomic study of the genus Lateantenna<D> Amsel, 1968 (Lepidoptera: Blastobasidae) from Mainland China, with descriptions of four new species - Teng, Kaijian; Wang, S. (Entomologica Fennica, 2019)
The ten species of the genus Lateantenna Amsel, 1968 known from China are reviewed. Four new species are described: L. semicircularis sp. n. and L. zhejiangensis sp. n. from Zhejiang, L. lunata sp. n. from Yunnan and Hainan, and L. triangulata sp. n. from Yunnan. Lateantenna eurotella (Adamski, 2010) and L. ianella (Adamski, 2003) are newly recorded for China. The females of L. camelliae (Chen & Wu, 2013) and L. ianella (Adamski, 2003) are described for the first time. Photographs of adults and genitalia are provided. Based on male genitalia, a key to the species of Mainland China is provided. Two maps showing the distribution of these species are also included.